Sustainable Earth Battery for Power Generation - Siti Rawiah Zulkipli,; Kamarudin, Mudzaffar Syah; Zaidi Embong, (Enhanced Knowledge in Sciences and Technology, 2024)
The advanced world urges people to grow with the development of recent technologies continuously. Hence, the demand for power supply and electricity increases over time. Nowadays, the gaps to fulfill this essential need are to approach a clean and sustainable source of energy according to the sustainable development goals to ensure access to affordable, reliable, and modern energy for all. In this study, it is observed that current issues on energy storage known as battery energy storage are despite it is convenience to use and availability, the dangerous chemicals contained in it are affecting nature and living life in the long run when it is disposed handle carelessly. This research aims to find alternative eco-green energy sources by generating soil electricity. This study investigated the ability of different types of soils, clay soil, barren soil, and peat soil from Parit Botak, Johor, and Pagoh, Johor to generate voltage. The voltage values were gained by using two different types of electrolytes, distilled water and tamarind water. These soils' morphological structure and elemental compositions were characterized using Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX). The average voltage values gained for clay soil, barren soil, and peat soil with distilled water are 11.73 V, 13.44 V, and 7.30 V while for tamarind water are 8.554 V, 7.190 V, and 9.70 V respectively. Subsequently, elemental analysis by EDX shows that clay soil's main elemental ion consists Al (7.01%), followed by Fe (1.55%) and K (0.77%), then for barren soil, led by Al (11.25%) and Cu (0.54%), and in peat soil consists of Al (5.36%) and K (0.88%). Collectively, the presence of these elemental ions found by SEM-EDX shows the soil's capability of electron flow for generating electricity hence between these three types of soil, it is observed that barren soil with distilled water generates the highest voltage value an average of 13.44 V.